Omega-3/omega-6 fatty acids: The effects on the psychophysical well-being of adolescents and adults - Giulio Perrotta (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2023)
Background: Fatty acids of the omega-3/omega-6 groups are used especially in cases of pregnancy, lactation, and malnutrition. In recent decades, pediatrics has been trying to find out whether the use of omega-3/omega-6 has effects on human growth and neurodevelopment. Aims: Check the state of the art on the use of omega-3/omega-6 type fatty acids in the diet, in adolescent and adult populations. Materials and methods: A total of 72 original articles on the topic of human growth and nutrition in pediatrics have been selected on PubMed through September 2022. Results: In literature, the use of omega-3/omega-6, with greater prevalence in the former group than the latter group, appears to be most effective in hypertension hypothesis, dyslipidemia, and high C-reactive protein values, cardiovascular risk, and neuropathic pain, while appearing to have less impact on neurodegenerative (except in multiple sclerosis) and mental disorders (except in depression). Interesting benefits can be detected when combining omega-3/omega-6 with spirulina algae, chitosan, probiotics, vitamin D, fiber and plant extracts.  Conclusion: Significant evidence emerges on the importance of omega-3 and omega-6 fatty acid supplementation, but important structural shortcomings of research designs still emerge from the published studies; moreover, many studies assume that fatty acid supplementation can have a curative effect on already active diseases, when in fact such prescriptions should be considered as adjuvant therapies to prevent or promote symptomatic regression, precisely because of their anti-inflammatory, antioxidant and immunomodulating virtues. However, there is no concrete and robust evidence of the positive impact on psychological well-being. Future research that can resolve the critical issues highlighted is hoped to promote a better approach to the topic of omega-3/omega-6 supplementation in human health.